2023
DOI: 10.1002/ajb2.16177
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pollen:ovule ratios: Evolutionary consequences of pollinator dependence and pollination efficiency for pollen and ovule production in angiosperms

Abstract: Premise: The relative per-flower production of ovules and pollen varies broadly with angiosperm mating systems, with outcrossing types commonly producing more pollen grains per ovule than selfing types. The evolutionary causes of this variation are contentious, especially the relevance of pollination risk. Resolution of this debate may have been hampered by its focus on pollen:ovule (P:O) ratios rather than on the evolution of pollen and ovule numbers per se. Methods: Using published mean ovule and pollen coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…With increasing pollen production, PTE decreases for Erica species, which is consistent with findings from other studies ( Harder and Johnson 2023 ). This could be caused by plant species with less efficient pollinators compensating for low PTE with increased pollen production as a strategy that ensures reproductive success.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With increasing pollen production, PTE decreases for Erica species, which is consistent with findings from other studies ( Harder and Johnson 2023 ). This could be caused by plant species with less efficient pollinators compensating for low PTE with increased pollen production as a strategy that ensures reproductive success.…”
Section: Discussionsupporting
confidence: 92%
“…However, even though relatively high for plants with granular pollen, PTE in the sampled Erica species is still relatively low compared to values of up to 40% recorded for some orchids ( Johnson et al 2005 ; Hobbhahn and Harder 2016 ) and asclepiads ( Shuttleworth and Johnson 2008 ) that produce aggregated pollen in the form of pollinia. There is generally a negative relationship between PTE and pollen production ( Gong and Huang 2014 ; Harder and Johnson 2023 ), which suggests that production of pollen may evolve in relation to the risk of it being lost in transit between flowers ( Harder and Johnson 2023 ). Relatively low pollen-ovule ratios in Erica may reflect the aggregation of pollen in tetrads and high PTE in this genus ( Harder and Johnson 2008 ; Arendse et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was also largely confirmed by our controlled hand pollinations and by pollen viability and stigma receptivity. However, recent research has shed light on the impact of pollinator dependence and pollination efficiency on the evolution of pollen number per flower, indicating that their influence is more pronounced in this aspect compared to ovule number [ 72 ]. Interestingly, in the case of M. tommasinii , the number of pollen grains per flower aligns with the observed pollen-ovule ratios.…”
Section: Discussionmentioning
confidence: 99%
“…[46,[92][93][94]) pollen economy seems to vary little among species with ovule number. For example, recent studies have demonstrated that pollen production per flower varies positively with latitude but ovule number does not [95], and that transfer efficiency varies positively with pollen production but not with ovule production [43]. Therefore, the evolution of pollen economy probably occurs largely independently of the evolution of ovule production.…”
Section: (C) Functional Evolution Of Pollen Dispersalmentioning
confidence: 99%
“…Pollen aggregations, known as pollinia, attach to pollinators via a sticky pad (viscidium) in most orchids (Epidendroideae and Orchidoideae) or a mechanical clasper (corpusculum) in milkweeds (Secamondoideae and Asclepiadoideae). Flowers with pollinia produce approximately as many individual pollen grains as do those with monads [ 43 , 44 ]. Solid pollinia of most orchids (approx.…”
Section: Introductionmentioning
confidence: 99%